Costs and Outcomes of Clostridioides difficile Infections in Germany: A Retrospective Health Claims Data Analysis - Katharina Schley; Kirstin Heinrich; Jennifer C. Moïsi; Dennis Häckl; Dominik Obermüller; Gordon Brestrich; Christof von Eiff; Thomas Weinke (Infectious Diseases and Therapy)
Abstract Introduction Health claims data are a valuable resource for health services research, enabling analysis of the costs of hospitalizations, outpatient visits, procedures, and medications, and providing an improved understanding of the economic burden and underlying cost drivers for a given health condition. Since no recent data were available from Germany on the medical costs and clinical outcomes of Clostridioides difficile infections (CDI), this study assessed the economic burden of CDI and all-cause mortality in adults in Germany. Methods A retrospective cohort study was conducted using a large, anonymized administrative health claims research database from Germany from which an age- and sex-representative sample of 4 million insured persons covered by approximately 60 statutory health insurances was extracted. Propensity score matching was conducted on age, sex, comorbidities, and antibiotic use to identify four matched controls (i.e., patients without CDI) for every eligible adult patient with CDI (i.e., case) in the study cohort. Costs, healthcare resource utilization, and CDI-attributable all-cause mortality were assessed. Results Overall, there were 15,342 CDI cases in the study cohort. One-year mortality in CDI cases (45.7%) was more than fourfold that of matched non-CDI controls (11.0%). In the year following the index date, average mortality-adjusted medical costs per person-time for CDI cases were almost fivefold that of matched non-CDI controls, representing a cost difference of €31,459, mainly driven by inpatient treatment. Overall excess costs for CDI cases were estimated at approximately €1.6 billion within 1 year after diagnosis. Conclusions CDI in Germany is associated with a high clinical and economic burden, including significantly higher mortality, costs, and healthcare resource utilization, in patients with CDI versus their matched patients without CDI. This has important implications for patients, healthcare providers, and the healthcare system.